ANALISIS POTENSI DAN EFEKTIVITAS PENERIMAAN PAJAK PENERANGAN JALAN DI KOTA MANADO - Pandelaki, Meggy Marchia; Sabijono, Harijanto; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The street lighting tax is one of the district / city taxes imposed on the use of electricity provided that street lighting is available in the area, whose accounts are paid by the regional government. Street lighting tax is one of the potential sources of regional income that can be influenced by certain factors. Therefore, this study aims to determine the potential and tax effectiveness of street lighting in the Regional Revenue Office of the City of Manado. The analytical method used is qualitative descriptive analysis. The data sources used in this study are secondary data, namely data originating from the Regional Revenue Office of the City of Manado. The results of the study indicate that the potential for street lighting tax in Manado City is less effective, and the tax effectiveness of street lighting from 2013-2017 is very effective. In 2013 the highest effectiveness of street lighting tax was 105.82 with very effective criteria, and in 2016 the lowest effectiveness of street lighting tax was 100.87 with very effective criteria. This means that tax on street lighting is very efficient and good, because the realization of street lighting tax revenues in the city of Manado reaches its real revenue potential.Keywords: Potential, Effectiveness.